Ambient Air VOC Levels in an Industrial Area of Turkey: Levels, Spatial Distribution, and Health Risk Assessment - Aykan Karademir; Ercan Arpaz; Şenay Çetin Doğruparmak; Gülsün Özgül (Toxics)
The seasonal variations, spatial distribution, and health risk assessment of 13 volatile organic compounds (VOCs), particularly benzene, toluene, ethyl benzene, and xylene (BTEX), in the ambient air of Dilovası, a Turkish city with unplanned urbanization, are presented in this study. Using passive tube sampling, at 22 locations in Dilovası, air samples were collected separately for the summer and winter, and concentrations were measured using thermal desorption GC-MS. Pollution maps were created using the Golden Software Surfer program and QGIS Desktop 3.42.0 software program. A health risk evaluation was conducted using the US Environmental Protection Agency’s (USEPA) approach. The study’s findings demonstrated that the atmospheric VOC concentrations at the sampling locations varied significantly by season and location. According to a carcinogenic risk assessment, residents in this area may be more susceptible to cancer if they are exposed to benzene, ethylbenzene, and naphthalene over an extended period. A non-carcinogenic risk (HQ) evaluation determined that while there was no significant risk at 21 measurement points, there was a substantial risk for non-cancer health effects at 1 measurement point. The significance of regulatory policies and pollution control technologies has once again emerged in this context.